Macro and microelement analysis of Sargassum fluitans and Sargassum natans arriving in the coastal zone of Cancun, Quintana Roo, Mexico (Revista de Biología Marina y Oceanografía, 2022)
In recent years, the massive increase in Sargassum landings on the Mexican Caribbean coast has generated negative environmental repercussions. This study has two main objectives (1) to analyze the macro and micronutrients of Sargassum fluitans and S. natans in order to (2) use them in the local and regional industry as a biofertilizer in the production of ornamental plants. Sargasso samples were collected from floating arrivals in the sea and landfall in the area of three beaches in Cancun, Quintana Roo, Mexico in 2018. The quantification of the elements in the samples was carried out using the method of fundamental parameters. The concentration of the macronutrients Ca, Na, K and Cl was higher than the elements Mg, S, Si and Sr, as well as two orders of magnitude higher than Al and P. Additionally, the trace elements Fe, Mn, Zn, Cu, and Ni were found in both species. It is worth mentioning that most of these elements are essential to complete the life cycle of plants; therefore, S. fluitans and S. natans can be considered as an excellent natural resource and alternative as a soil improver for the cultivation of ornamental plants.